PEDAGOGICAL CONDITIONS OF FORMATION OF READINESS FOR SELF CADETS SYSTEM UKRAINE - Жукевич, І. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article defines the purpose of the study, which is to identify and substantiate pedagogical conditions of formation of readiness for self-education students of higher educational institutions of the MIA of Ukraine. The essence of concepts "motivation", "self-work", "information competence", "self-education." The pedagogical conditions of formation of readiness for self-education of cadets of higher educational establishments of the Ministry of Internal Affairs of Ukraine, namely the development of self-motivation and organizational skills of cadets; formation of information competence of cadets; effective organization of self work of cadets; self-actualization in the educational process are determined